The Effect Of Ethanolic Bee Pollen Extract From Geniotrigona Thoracica On Dna Damage And Dna Methylation In Ht-29 Colorectal Cell Line - Harif Fadzilah, Nurdianah (2022)
This study aims to investigate the protective effect of stingless bee pollen against DNA damage and to measure the effect of bee pollen on global DNA methylation.